Evaluation of riboflavin, nanocurcumin, and hydrogen peroxide under light conditions: Reduction of mature dental biofilms and enamel mineral loss - Shima Afrasiabi; Ahmed Qays Khudhur AL． Gburi; Ladan Ranjbar Omrani; Nasim Chiniforush; Zohreh Moradi (Photodiagnosis and Photodynamic Therapy)
Background: Biofilms are a potential harbor for many microorganisms. The aim of this study was to test the efficacy of riboflavin (Rib), nano-micelle curcumin (NC), and hydrogen peroxide (HP), alone and in combination with the respective light (light-emitting diode (LED) or 980 nm diode laser) on the reduction of Streptococcus mutans and Lactobacillus acidophilus dual-species biofilms and their effect on the enamel mineral loss. Materials and methods: The biofilms were formed on saliva-coated enamel slabs. Then, the biofilms were treated with antimicrobial photodynamic therapy (PDT) based on LED, Rib, and NC photosensitizers and with HP also based on a 980 nm diode laser (n = 8 per group). A crystal violet assay was performed to determine the reduction of the dual-species biofilms. The enamel slabs were analyzed for calcium and phosphorus content by scanning electron microscopy (SEM) and energy dispersive X-ray spectroscopy (EDX). Results: While HP-PDT showed a reduction of 37% (p < 0.001), PDT with NC resulted in an even greater reduction of dual-species biofilms (40%, p < 0.001) than HP- and Rib-mediated PDT. In the EDX test, no significant difference was found between the control group and the treatment groups. Conclusions: The use of natural photosensitizers such as NC in PDT has an effect that may be potentially important in reducing caries-causing bacteria.